Makna Kekerasan Seksual dan Stigma Masyarakat Terhadap Korban Kekerasan Seksual: The Meaning of Sexual Violence and Society Stigma Against Victims of Sexual Violence - Siti Mas'udah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
Sexual violence is a serious issue that is becoming more common in various forms. The number of victims of sexual violence is growing, and its forms are becoming more diverse. This study aims to reveal the meaning of sexual violence to victims or survivors and the social sanctions they face. This study employed mixed-method research, with 377 respondents interviewed. According to the findings of this study, victims perceive sexual violence as a bad, embarrassing, and inappropriate experience. The victims were subjected to social sanctions from the community, including friends, neighbors, and social media users. The Law of Sexual Violence Crime Number 12 of 2022 demonstrates the state’s efforts to achieve gender justice. This study recommends the need to protect victims of sexual violence from families, communities, society, and the state to realize gender equality.